Effectiveness of Benson relaxation therapy on prenatal anxiety among mothers in a tertiary care hospital, Kochi - S., Harichandana; Thurkkadayil, Anju Philip (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The purpose of the study is to evaluate the effectiveness of the Benson relaxation therapy on prenatal anxiety among mothers. Methods: An experimental pre-test and post-test study were conducted among 30 antenatal mothers who were admitted to antenatal wards of a tertiary-level hospital. The antenatal mothers with gestational age 28 and above, with anxiety score above 21 according to the Prenatal Anxiety Screening Scale (PASS) were included in the study, and mothers with a history of substance dependence, psychotic disorders, or any other major psychiatric disorders, and epilepsy were excluded from the study. Probability sampling was used. Data were collected after ethical clearance and informed consent. Following to the pre-test, which includes a collection of demographic data, the antenatal mothers in the experimental group received the Benson relaxation therapy. And post-test was conducted among both groups on the fifteenth day. Results: The mean age group of the antenatal mothers were in age group of 26-33 years. 46.7% of samples have a secondary level of education. The majority (53.3%) are self-employed. Sixty percent of the mothers are primigravida. Fifty-seven percent are residing in a rural area and belong to joint family. There is a significant difference between the post-test score of the experimental and control group at the p=0.001 level. The Benson relaxation therapy is effective in reducing prenatal anxiety among antenatal mothers. Conclusions: Benson relaxation therapy is a simple, effective and mind-body relaxation technique to relieve anxiety among pregnant women.